Non-selective feeding on microplastics in the acorn barnacle Amphibalanus amphitrite: the implications in assessing barnacles as global microplastics bioindicators - Wang, Yixuan; Wong, Alex Chun Yuen; Chiu, Jill Man Ying; Cheung, Siu Gin (Frontiers in Marine Science, 2025)
To combat the plastic problem in the marine environment, bioindicators are essential because they can provide insights into the extent and ecological impacts of plastic pollution. The ingestion and accumulation of microplastics (MPs) in the striped barnacle Amphibalanus amphitrite was studied by exposing them to MPs with or without biofilm. Three types (polyethylene, polystyrene/polyester), two sizes (27-32 µm and 90-106 µm) and two forms (microspheres and microfibers) of MPs at three concentrations (7.2, 72 and 720 P/mL) were investigated. The presence of biofilm did not affect the MP ingestion. The ingestion of MPs was concentration-dependent, irrespective of the size, form and type of the MPs. The numbers of microspheres and microfibers ingested by A. amphitrite were similar, and so were their numbers accumulated in the body. The results suggest a lack of both pre-ingestive and post-ingestive sorting and removal of MPs in A. amphitrite. The MP body burden, therefore, reflects levels of environmental contamination and the actual MPs composition in the water body. Considering the global distribution of A. amphitrite and its high abundance on rocky shores and man-made structures such as wharf piles, ease of finding and sampling, clear taxonomic status, small body size, high reproductive rate, specialized feeding mode, and well-known biology and life history, it has great potential to be considered as a member of a list of global marine bioindicators of MPs. Further investigations should focus on how seasonal changes in environmental factors and body conditions, such as reproductive cyclicity, influence the ingestion and accumulation of MPs, and the associated ecotoxicological effects.